The Immediate Effect of COVID-19 Vaccination on Anticoagulation Control in Patients Using Vitamin K Antagonists - Visser, Chantal; Biedermann, Joseph S.; Nierman, Melchior C.; van der Meer, Felix J.M.; Gulpen, Anouk J.W.; Moors, Yvonne C.F.; Cannegieter, Suzanne C.; Lijfering, Willem M.; Kruip, Marieke J.H.A.; on behalf of the Dutch COVID & Thrombosis Coalition (Thrombosis and Haemostasis, 2022)
Background In January 2021, the Dutch vaccination program against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was started. Clinical studies have shown that systemic reactions occur in up to 50% of vaccine recipients. Therefore, COVID-19 vaccination could affect anticoagulation control, potentially leading to an increased risk of thrombotic events and bleeding complications.Aims This article investigates whether the BNT162b2 vaccine affects anticoagulation control in outpatients using vitamin K antagonists (VKAs).Methods A case-crossover study was performed in a cohort of outpatient VKA users from four Dutch anticoagulation clinics who received a BNT162b2 vaccine. International normalized ratio (INR) results and VKA dosages before the first vaccination, the reference period, were compared with those after the first and second vaccination.Results A total of 3,148 outpatient VKA users were included, with a mean age (standard deviation) of 86.7 (8.7) years, of whom 43.8% were male, 67.0% used acenocoumarol, and 33.0% phenprocoumon. We observed a decrease of 8.9% of INRs within range in the standard intensity group (target INR 2.0–3.0). There was both an increased risk of supratherapeutic (odds ratio [OR] = 1.34 [95% confidence interval [CI] 1.08–1.67]) and subtherapeutic levels (OR = 1.40 [95% CI 1.08–1.83]) after first vaccination. In the high-intensity group (target INR 2.5–3.5), the risk of a supratherapeutic INR was 2.3 times higher after first vaccination (OR = 2.29 [95% CI 1.22–4.28]) and 3.3 times higher after second vaccination (OR = 3.25 [95% CI 1.06–9.97]).Conclusion BNT162b2 was associated with an immediate negative effect on anticoagulation control in patients treated with VKAs, so it is advisable to monitor the INR shortly after vaccination, even in stable patients.
Keywords: acenocoumarol; phenprocoumon; BNT162b2 vaccine; COVID-19 vaccines; anticoagulants